The Route of Infection Influences the Contribution of Key Immunity Genes to Antibacterial Defense in Anopheles gambiae - Amira San Dekmak; Xiaowei Yang; Heinrich Zu Dohna; Nicolas Buchon; Mike A. Osta (Karger Publishers, 2020)
Insect systemic immune responses to bacterial infections have been mainly studied using microinjections, whereby the microbe is directly injected into the hemocoel. While this methodology has been instrumental in defining immune signaling pathways and enzymatic cascades in the hemolymph, it remains unclear whether and to what extent the contribution of systemic immune defenses to host microbial resistance varies if bacteria invade the hemolymph after crossing the midgut epithelium subsequent to an oral infection. Here, we address this question using the pathogenic Serratia marcescens (Sm) DB11 strain to establish systemic infections of the malaria vector Anopheles gambiae, either by septic Sm injections or by midgut crossing after feeding on Sm. Using functional genetic studies by RNAi, we report that the two humoral immune factors, thioester-containing protein 1 and C-type lectin 4, which play key roles in defense against Gram-negative bacterial infections, are essential for defense against systemic Sm infections established through injection, but they become dispensable when Sm infects the hemolymph following oral infection. Similar results were observed for the mosquito Rel2 pathway. Surprisingly, blocking phagocytosis by cytochalasin D treatment did not affect mosquito susceptibility to Sm infections established through either route. Transcriptomic analysis of mosquito midguts and abdomens by RNA-seq revealed that the transcriptional response in these tissues is more pronounced in response to feeding on Sm. Functional classification of differentially expressed transcripts identified metabolic genes as the most represented class in response to both routes of infection, while immune genes were poorly regulated in both routes. We also report that Sm oral infections are associated with significant downregulation of several immune genes belonging to different families, specifically the clip-domain serine protease family. In sum, our findings reveal that the route of infection not only alters the contribution of key immunity genes to host antimicrobial defense but is also associated with different transcriptional responses in midguts and abdomens, possibly reflecting different adaptive strategies of the host.